THE INFLUENCE OF PROBLEM-BASED LEARNING ASSISTED BY MATHICA TO IMPROVE THE PROBLEM-SOLVING ABILITY OF ELEMENTARY SCHOOL STUDENTS - Lisa Virdinarti Putra; Ela Suryani; Tri Sundari Lia Oktaviani (FIP Unimed, 2022)
This study aims to determine whether the Problem-Based Learning Model assisted by Mathica influences the ability to solve mathematical problems in fifth grade students. The results of the statistical inference analysis showed that in the Wilcoxon test there was a significant difference between the problem-parameter scores of the problem-solving ability of the VA model assisted by Mathica Problem Based Learning and the parameter scores of the problem-solving ability of students in the V class model problem-based learning. From the results of this study, conclusions were drawn about the influence of Mathica-assisted Problem-Based Learning Models on students' problem-solving abilities.